2014
DOI: 10.15171/ijhpm.2015.08
|View full text |Cite
|
Sign up to set email alerts
|

Understanding perception and factors influencing private voluntary health insurance policy subscription in the Lucknow region

Abstract: Background: Health insurance has been acknowledged by researchers as a valuable tool in health financing. In spite of its significance, a subscription paralysis has been observed in India for this product. People who can afford health insurance are also found to be either ignorant or aversive towards it. This study is designed to investigate into the socio-economic factors, individuals' health insurance product perception and individuals' personality traits for unbundling the paradox which inhibits people from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
(28 reference statements)
2
17
0
1
Order By: Relevance
“…The result shows consistency with earlier studies. It supports the findings of Mathur et al, (2014) who reports that families with large number of dependants in Lucknow region, India demonstrate low propensity to subscribe to health insurance compare to household with lesser dependants. Also, Fletschner and Kenney (2014) discover that responsibility imposed on rural women as a result of family size is a factor for determining their financial services (insurance inclusive) need and ability to obtain it.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…The result shows consistency with earlier studies. It supports the findings of Mathur et al, (2014) who reports that families with large number of dependants in Lucknow region, India demonstrate low propensity to subscribe to health insurance compare to household with lesser dependants. Also, Fletschner and Kenney (2014) discover that responsibility imposed on rural women as a result of family size is a factor for determining their financial services (insurance inclusive) need and ability to obtain it.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…The size of the family determines the perception and subscription to health insurance among residents of Lucknow region, India. Mathur, Paul, Prasad and Das (2014) discover that families with large number of dependants demonstrate low propensity to subscribe to health insurance compare to household with lesser dependants.…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also because of fearing future health costs when family members might become sick [1,2]. However, this finding is contradictory to the study conducted in Burkina Faso [26][27][28]. The inconsistency might be due to the fact that households' apprehensions (fears) about the compromise of quality of service they would be consuming during the enrollment time.…”
Section: Discussionmentioning
confidence: 88%
“…The studies conducted in Ghana and India had shown that families with an illness at least in one member in the past one year were more likely to will to enroll in to insurance scheme than the counterparts and that witnessed the effect of adverse selection on enrolment decision. The more households experience health problems, the more expense they would make for each healthcare consumed and thus households decide to enroll in to any risk poling programs because of fearing future expensive health expense when family members might get in to sick (1,12), However this finding is contradictory to a the study conducted in Burkina Faso (22). This inconsistency might be due to the fact that households' apprehensions (suspections) about the compromization of quality of service they would consumed during the enrolment time.…”
Section: Discussionmentioning
confidence: 92%